Impact of Estrogen on Anthropometric Indices of Normal Menstruating and Menopausal Type-II Diabetic Females - Ansari, Shafaq; Warsi, Jamshed; Laghari, Zulfiqar (Journal of Liaquat University of Medical & Health Sciences, 2021)
Objective: To determine and compare the anthropometric measures between normal & Type-II Diabetic menstruating and menopausal women. Methodology: A cross sectional study, conducted at the Physiology Department University of Sindh (UoS) from January to December 2019. The diabetic females were recruited from Liaquat medical hospital (LUH) Jamshoro/Hyderabad and menopausal women from society. The sample size was calculated by EP info Software. Total 200 females were included in this study. The purpose of study was explained and verbal and written consent was taken from all participants. After taking all anthropometric parameters, 3ml of blood was drawn for biochemical analysis, and stored in Laboratory at -200C. Results were entered and analyzed by SPSS 19.0 Version by applying ANOVA- Post hoc test for continuous variables. Results: The results of all Anthropometric parameters of Menstruating normal, menstruating diabetics, menopausal normal, menopausal diabetic were reported significant p. value (<0.001) except results of height and neck circumference which were insignificant. Conclusion: Fluctuation of serum estrogen in pre and post-menopausal females were arbitrated to developed obesity and T2DM and also alter the anthropometric indices. Key Words: Diabetes Mellitus, Menopause, Estrogen.